Synopsis of Paraguayan Civil Procedure Law and the desire for its humanization (Legal journal - Research in Legal and Social Sciences, 2017)
Coinciding with the commemoration of the 200 years of independent life of the Republic of Paraguay, we consider it opportune and necessary to carry out a study regarding the transcendental aspects of the evolution of Paraguayan civil procedural law, highlighting the various normative instruments that have governed our Republic. , the attempt to reform with the presentation of various projects throughout our history and, especially, the fundamental aspects of the General Procedural Code project, with which we can disagree on many aspects, but what is significant and transcendental is that laid the foundations to generate a debate regarding the urgent need for reform in this branch of legal science. In the same way, the modern practices and tools in force in comparative civil procedural law are exposed, which aim to speed up the process, access to justice for all, all at a lower cost. The most important thing is that there is still much to be done, due to the shortcomings of the system, especially in the field of the administration of justice and in the normative order.
Keywords: digitization of the process; National Constitution; humanization; Civil procedural law